KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI MENGAJAR GURU DI SMP SWASTA AMAL BAKTI MEDAN - Hennny Ramdaniar (Universitas Labuhanbatu, 2022)
This study aims to determine the leadership of the principal at Amal Bakti Private Middle School Medan, then the efforts of the principal in increasing teacher teaching motivation, and reveal the principal's leadership and teacher motivation at Amal Bakti Private Middle School Medan. The population in this study were principals and teachers, totaling 11 people. The results of interviews in the field with the principal and some of the teachers at Amal Bakti Private Middle School Medan, the conclusion is that the principal's leadership in increasing the motivation of teachers at the school is the first to be carried out by looking at the operational management of the school, by implementing the curriculum and teaching students, teacher personnel , and administrative personnel, facilities and infrastructure, finances, as well as relations with parents and relatives of students, always tend to apply the democratic type. In an effort to increase teacher motivation to teach, steps are taken to improve teacher welfare, school financial transparency, always open dialogue with teachers as often as possible, give awards to outstanding teachers, and continuously complement facilities and infrastructure. The influence of the principal's leadership on increasing teacher motivation to teach can occur well due to a sense of togetherness, a sense of kinship, a sense of belonging, a sense of responsibility and a growing desire to move forward together.Key Words : Principal Leadership, Increasing Teacher's Teaching Motivation.